Publication performance vs. influence: On the questionable value of quality weighted publication rankings - Justus Haucap; Tobias Thomas; Klaus Wohlrabe (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2017)
In broad parts of the scientific community the position in publication performance rankings, based on journal quality ratings is seen as highly reputational for the scientist. This contribution provides evidence that, at least in economics, such publication performance measures can not always be reconciled with measures for academic influence such as citation-based measures. We analyze data from the Scopus database as well as from the prestigious German-based Handelsblatt ranking for 100 renowned economists (lifetime achievement). Scholarly influence is proxied by various bibliometric indicators such as the number of citations, the h-index, the citations of the most cited paper as well as the hardly honorable Pi-Beta-score ("Publications Ignored, By Even The Author(s)"). We argue that publication performance measures based on journal ratings, such as the Handelsblatt rankings, are not good proxies for an economist's impact within the scientific community. From this perspective the value of publication performance rankings based on journal quality ratings is questionable.
Keywords: A12; A14; 330; economics; academic reputation; academic rankings; influence; citations; Scopus; Handelsblatt ranking; academic journals